2008
DOI: 10.1007/s10800-008-9680-6
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric study of the influence of benzotriazole on copper deposition from a sulphuric plating bath

Abstract: Copper electrodeposition on to a platinum substrate from an acid sulphate plating bath was investigated with and without the additive benzotriazole (BTAH). In voltammetric experiments, the deposition process is shifted to more negative potentials in the presence of BTAH than in its absence from the bath. Moreover, the current density of the deposition process was higher in the presence of this additive than in its absence. With or without the additive, copper deposition showed features of nucleation in the vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…At low current density values, the summation of copper and zinc partial current densities is always smaller than the applied current density value. Moraes et al [37] have shown that the contribution of the HER to copper electrodeposition process in acid medium was more significant in the presence of BTAH. In fact, the HER curve is near the total curve, showing its contribution to the process.…”
Section: Electrodeposition Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…At low current density values, the summation of copper and zinc partial current densities is always smaller than the applied current density value. Moraes et al [37] have shown that the contribution of the HER to copper electrodeposition process in acid medium was more significant in the presence of BTAH. In fact, the HER curve is near the total curve, showing its contribution to the process.…”
Section: Electrodeposition Experimentsmentioning
confidence: 99%
“…7a, they also show several pores and cracks, which can facilitate the corrosion attack of the substrate. Moraes et al [37] have already demonstrated that the addition of BTAH to a bath for copper deposition produced less crystalline coatings when compared with a bath free of this additive. However, after the corrosion experiment, this coating (which presented a gray-yellowish color) turned yellow.…”
Section: Electrodeposition Experimentsmentioning
confidence: 99%
“…Deposition of copper from aqueous sulphuric acid containing copper sulfate is widespread in industry due to the speed of the electrodeposition process, the relatively low cost, and the ease of control and maintaining the electrondeposition 5 . Furthermore, it is possible to obtain uniform, ductile, and strong coatings 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding sulphuric plating baths, the effect of additives such as thiourea 9,10 , gelatin 9 , benzotriazole 5,11,12 , DPS (3-N,Ndimethylaminodithiocarbamoyl-1-propanesulphonic acid) and PEG (polyethylene glycol) 13 have been studied.…”
Section: Introductionmentioning
confidence: 99%